Emotional Intelligence as Correlate of Job Satisfaction and Commitment among Secondary School Counsellors in Kano State, Nigeria - SANUSI, Muhammad Kani (Ilorin Journal of Education, 2024)
The study aims at studying emotional intelligence as correlate of job satisfaction and commitment among secondary school counsellors in Kano State, Nigeria. The research design adopted for this study is correlational design. The population for this study was made up of 1,505 secondary schools’ counsellors in Kano State. The sample of the study comprised of 740 secondary schools’ counsellors (497 males and 243 females). Instruments for data collection in the study were researcher designed questionnaires titled ‘Secondary School Counsellor’s Emotional Intelligence Questionnaire (SSCEIQ)’ and ‘Secondary School Counsellor’s Job Satisfaction Questionnaire (SSCJSQ)’ and School Counsellor’s Job Commitment Questionnaire (SSCJCQ). Pearson Correlation analysis was used to analyse the data. Findings of the study include the relationship between emotional intelligence and job satisfaction and emotional intelligence and job commitment of counsellors was very high positive relationship with a significant relationship between emotional intelligence and job satisfaction. It is recommended among others that government should be interested in the counsellors’ emotional intelligence, job satisfaction and commitment because they influence counsellors’ behavior. Education managers should raise the counsellors’ emotional intelligence, job satisfaction and commitment by focusing on the intrinsic and extrinsic parts of the school counselling.